New possibilities of correction of metabolic disorders in women with PCOS - Л. В. Калугіна; Т. Ф Татарчук (Publishing House TRILIST, 2018)
The aim of the study, the results of which are described in the article, was to study the possibilities of using a polycomponent drug containing D-kiro-inositol in the polycystic ovarian syndrome. A comparative prospective study was conducted with the participation of 60 patients of reproductive age suffering from polycystic ovarian syndrome (phenotype A). The criteria for participation in the study were: a confirmed diagnosis of polycystic ovarian syndrome with ovarian enlargement and oligo/anovulation and a raised level of ovarian androgens; body mass index from 26 to 30 kg/m2. Patients with severe endocrine and somatic pathology were excluded from the study. Women aged 18-35 years were on out-patient treatment in the Endocrine gynecology department of the SI "Institute of Pediatrics, Obstetrics and Gynecology of the NAMS of Ukraine". By random sampling, the patients were divided into 2 groups of 30 people each. For 6 months, the patients of the main group received twice a day 1 Protalis complex drug containing D-kiroinositol, which is recommended for normalization of ovarian function and stimulation of spontaneous ovulation in polycystic ovarian syndrome, improvement of oocyte state, and also to promote reduction of oxidative and inflammatory stress, reducing the level of total testosterone and increasing fertility. Patients of the control group received recommendations on dietary nutrition and exercise. Analysis of the results of therapy showed a recovery in the main group of regular ovulatory menstrual cycles in 53.33% of cases, a decrease in the frequency of androgen-dependent dermatopathy by 50%, normalization of body weight and a reliable decrease in androgen levels. In addition, a positive effect on metabolic parameters such as HOMA index and homocysteine level was noted. The results of the study allow us to recommend the use of Protalis course therapy (D-kiro-inositol and synergists) to restore ovulatory menstrual cycles, and as a means of preventing metabolic disorders in women with polycystic ovarian syndrome and overweight.